Jejak Perdagangan Bebas Cina di Situs Kota Cina dan Pulau Kompei - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2010)
AbstractNow, traces of free trade in the archipelago can not be separated from the past maritime trade activities, especially trade relations with Chinesse people. Past trading activity on the east coast of North Sumatera can be traced through the rest of the remains of material culture objects, particularly objects of material culture with respect to trading actvities. This can be traced through the remains of material cultural objects found on the site of Kota Cina dan Kompei Island located in the east coast of North Sumatera.